Ai margini del contado Terra, signoria ed élites locali a Sabbion e nel territorio di Cologna Veneta (secoli XII-XIII) - STELLA, Attilio (Reti Medievali E-Book, 2022)
In the twelfth and thirteenth centuries, during the emergence of the Italian communes, rural communities, increasingly populated and organised, imposed themselves as crucial actors in the relationship between city communes and rural lords, mostly thanks to the establishment of new local élites. The book offers a critical reassessment of this threefold dialectic in light of the rich documentation concerning Sabbion, near Cologna Veneta, in the eastern outskirts of the Veronese contado. This documentation has been preserved in the archives of San Giorgio in Braida of Verona, holder of the lordship over Sabbion, and enabled a detailed comparative analysis of the principal socio-economic and political changes of a small and relatively homogeneous society, its actions and agency.